Wavepackets in Boundary Layers Close to Transonic Speeds - Martínez, Andrés G.; Gennaro, Elmer Mateus; Medeiros, Marcello A.F. (Elsevier, 2015)
In practical situations, natural transition determines the transition to turbulence process. Experimental evidence suggest that the wave packet evolution is related closely to natural transition. The major part of numerical works on wave packets are focused on incompressible, supersonic and hypersonoc flows, subsonic ones are probably the less researched. A compressible DNS code was developed, several code validation tests were performed, including a simulation of an experiment of wave packets 1. The evolution of wave packets on compressible boundary layer in a flat plate is studied by Direct Numerical Simulations (DNS), to investigate the effect of Mach number in the initial nonlinear stages. For Mach 0.9 were considered three cases: linear, nonlinear and interaction between two packets. Results suggest that subharmonic mechanism is the most probable scenario at the initial nonlinear stages.
Keywords: Compressible boundary layer; DNS simulation; natural transition; subsonic boundary layer; wave packet